What Fuels the Boom Drives the Bust: Regulation and the Mortgage Crisis. (6th February 2017) - Dagher, Jihad; Fu, Ning
Abstract : The weakly regulated independent mortgage companies (IMCs) had a vastly disproportional contribution to the expansion in risky credit during the mortgage boom and to the ensuing foreclosure crisis. We exploit a quasi‐experimental setting, created by the inconsistency of state lender regulations between banks and IMCs and their heterogeneity across states, to isolate the impact of regulation on lending standards using county‐pairs straddling state borders. We find that weaker state regulation of IMCs is associated with a sharper expansion of IMCs, particularly in risky high‐yield loans, which were also of worse quality in the weakly regulated states, based on subsequent delinquency.